The Video Head Impulse Test (vHIT) of Semicircular Canal Function – Age-Dependent Normative Values of VOR Gain in Healthy Subjects - McGarvie, Leigh A.; MacDougall, Hamish G.; Halmagyi, G. Michael; Burgess, Ann M.; Weber, Konrad P.; Curthoys, Ian S. (Frontiers in Neurology, 2015)
Background/Hypothesis. The video Head Impulse Test (vHIT) is now widely used to test the function of each of the six semicircular canals individually by measuring the eye rotation response to an abrupt head rotation in the plane of the canal. The main measure of canal adequacy is the ratio of the eye movement response to the head movement stimulus i.e. the gain of the vestibulo-ocular reflex (VOR). However there is a need for normative data about how VOR gain is affected by age and also by head velocity, to allow the response of any particular patient to be compared to response of healthy subjects in their age range. In this study we determined for all six semicircular canals, normative values of VOR gain, for each canal across a range of head velocities, for healthy subjects in each decade of life. Study Design. The VOR gain was measured for all canals across a range of head velocities for at least 10 healthy subjects in decade age bands: 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, 80-89. Methods. The compensatory eye movement response to a small, unpredictable, abrupt head rotation (head impulse) was measured by the ICS Impulse prototype system. The same operator delivered every impulse to every subject. Results. VOR gain decreased at high head velocities, but was largely unaffected by age into the 80-89 year age group. There were some small but systematic differences between the two directions of head rotation, which appear to be largely due to the fact that in this study only the right eye was measured. The results are considered in relation to recent evidence about the effect of age on VOR performance. Conclusion. These normative values allow the results of any particular patient to be compared to the values of healthy people in their age range and so allow, for example, detection of whether a patient has a bilateral vestibular loss. VOR gain, as measured directly by the eye movement response to head rotation, seems largely unaffected by aging.